Knowledge Management (KM) Practices in Institutions of Higher Learning in Tanzania with Reference to Mbeya University of Science and Technology - Charles, Wilson; Nawe, J (University of Dar es Salaam Library Journal, 2017)
This study examined the knowledge management (KM) practices in Institutions of Higher Learning. Specifically, the study examined the level of awareness and understanding of KM among Mbeya University of Science and Technology (MUST) staff, and the existing knowledge management practices in addition to soliciting for the perceptions and opinions of staff on the current KM practices. Primary data were collected from 60 respondents comprising teaching and non-teaching staff using the questionnaire, face-to-face interviews and observation. The major findings of the study revealed that MUST staff were not explicitly aware of KM practices; there were no knowledge management initiatives in place at MUST; moreover, few or no strategies were employed in Managing knowledge; and there was no agreed upon mechanism for knowledge sharing. Thus, this study recommends establishing proper structure to promote and enhance KM practices in the institution. Also individuals should be encouraged to take on board knowledge management practices in their work. Furthermore, KM practices should be an integral part of the organisational culture.